Status Nutrisi dan Pertumbuhan Anak Usia 1-3 Tahun dan Hubungannya dengan Perkembangan - Amaliya, Sholihatul; Azizah, Nurona; Ambiasukma, Nanda Aji; Puteri, Alliya Avisa Insani (Poltekkes Kemenkes Bengkulu, 2024)
The first three years of life are an important period because there is very rapid growth and development. Developments in this period will determine the next stage and are influenced by many factors. This research aimed to understand the growth, nutritional status, and development of children aged 1-3 years and analyze the correlation of these 3 variables. This research was conducted in one area in East Java from October to December 2021 involving parents and children aged 1-3 years. Growth variables are assessed using indicators of body weight and body height according to age. Nutritional status is assessed by weight for height in WHO growth chart standards (z-score). Child development were assessed using the Kuesioner Pra Skrining Perkembangan (KPSP) instrument. The results showed that the majority of children had normal growth (60.6% and 63.9%), adequate nutrition status (83%), and normal development according to age (62.8%). Bivariate tests used chi-square test showed there was no relationship between growth and development (p = 0.255 and p = 0.461) and no relationship between nutritional status and child development (p = 0.246). It is necessary further study to explore other factors that might influence children's development and the government needs attention to develop programs that can reduce the rate of growth and development disorders.